Does gibberellin biosynthesis play a critical role in the growth of Lolium perenne? Evidence from a transcriptional analysis of gibberellin and carbohydrate metabolic genes after defoliation - Liu, Qianhe; Jones, Chris S.; Parsons, Anthony J.; Xue, Hong; Rasmussen, Susanne (Frontiers in Plant Science, 2015)
Global meat and milk production depends to a large extent on grazed pastures, with Lolium perenne being the major forage grass in temperate regions. Defoliation and subsequent regrowth of leaf blades is a major and essential event with respect to L. perenne growth and productivity. Following defoliation, carbohydrates (mainly fructans and sucrose) have to be mobilised from heterotrophic tissues to provide energy and carbon for regrowth of photosynthetic tissues. This mobilisation of reserve carbohydrates requires a substantial change in the expression of genes coding for enzymes involved in carbohydrate metabolism. Here we tested the hypothesis that gibberellins (GA) are at the core of the processes regulating the expression of these genes. Thus, we examined the transcript profiles of genes involved in carbohydrate and GA metabolic pathways across a time course regrowth experiment. Our results show that following defoliation, the immediate reduction of carbohydrate concentrations in growing tissues is associated with a concomitant increase in the expression of genes encoding carbohydrate mobilising invertases, and was also associated with a strong decrease in the expression of fructan synthesising fructosyltransferase genes. We also show that the decrease in fructan levels is preceded by increased expression of the GA activating gene GA3-oxidase and decreased expression of the GA inactivating gene GA2-oxidase in sheaths. GA3-oxidase expression was negatively, while GA2-oxidase positively linked to sucrose concentrations. This study provides indicative evidence that gibberellins might play a role in L. perenne regrowth following defoliation and we hypothesise that there is a link between gibberellin regulation and sugar metabolism in L. perenne.